Pengabdian Kepada Masyarakat: Hissi Berbagi Bersama Panti Asuhan Berkah Ilahi Palembang - Hana Pertiwi; Armasito; Ifrohati; Tutik Pebrianti (Jurnal Aksi Dosen dan Mahasiswa, 2024)
Service to Msyarakat is one of the three mandatory duties of lecturers listed in the tri dharma of higher education, as an implementation of the results that have been learned and can be beneficial to the wider community. Part of the service activity is social service, education and motivation for children in the orphanage, this activity aims to provide benefits to the community in the orphanage. This community service activity was carried out at the Palembang City Divine Blessing Orphanage. Several arrangements of activities such as compensation, motivation to children, and giving a little game (ice breaking) to the children in the orphanage, the service activities carried out at the Divine Blessing Orphanage went well after a series of events, as evidenced by the enthusiasm of the children in participating in these activities. In addition, all related parties also took part in the success of this service activity, which was attended by lecturers and the management of the Indonesian Association of Sharia Scholars (HISSI) South Sumatra. With this togetherness, it can provide a little help to meet the needs for them and benefits for the orphanage, share happiness with our brothers and sisters in the orphanage and can strengthen the bond of friendship between others and create a sense of mutual care and love for fellow humans on earth.